Prototipe Sistem Monitoring, Proteksi, dan Kontrol Putaran pada Mesin Emergency Generator Menggunakan Lora untuk Mencegah Kerusakan pada Sistem di Kapal - Andika Yogi Pratama; Edi Kurniawan; M. Dahri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In ship operations, the existence of a reliable emergency generator system is a critical factor to ensure continuity of electricity supply in emergency situations. Damage to the generator engine can cause significant disruption and even safety risks. To overcome this problem, a prototype monitoring, protection and rotation control system for emergency generator machines was developed using LoRa (Long Range) technology. This system is designed to monitor critical engine parameters, including speed, temperature and other operational conditions in real-time. Data collected from sensors is sent over a LoRa network that has wide coverage and low power consumption, enabling remote and continuous monitoring of Blynk's Internet of Think (IoT). This system is equipped with a protection algorithm that can detect anomalies and automatically activate corrective action or provide early warning to engineers and electricians. By implementing this prototype, it is hoped that it can reduce the risk of damage to the emergency generator engine and increase the reliability of the ship's electrical system, thereby supporting safer and more efficient operations.